Adhesive film, acrylic adhesive composition, and flexible device

By optimizing the formulation of the acrylic adhesive composition, an adhesive film capable of maintaining high bending, adhesion and cohesion under high and low temperature conditions was developed, which solves the problem of poor bending of the adhesive film under low temperature conditions in the prior art.

CN119752341APending Publication Date: 2025-04-04NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411382308.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-09-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing adhesive films have poor bending properties under low temperature conditions, and the low elastic modulus of the adhesive leads to a decrease in adhesion and weakening of cohesion, which makes it impossible to effectively withstand stress during bending.

Method used

An adhesive film containing an acrylic adhesive was developed. By optimizing the formulation of the acrylic adhesive composition, including acrylic polymers, oligomers and a variety of crosslinking agents, the adhesive film has high adhesion and cohesion at 23°C, and the energy storage modulus at -20°C is less than 140 kPa, maintaining high bending properties.

Benefits of technology

The adhesive film has achieved high bending, sufficient adhesion and high cohesion under both high and low temperature conditions, and can effectively withstand stress during bending, and is suitable for the manufacturing of flexible devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752341A_ABST
    Figure CN119752341A_ABST
Patent Text Reader

Abstract

Provided are: an adhesive film which can exhibit high bendability, sufficient adhesion to an adherend, and high cohesive force of an acrylic adhesive at the same time, and which comprises an adhesive layer comprising an acrylic adhesive, and a flexible device which is provided with such an adhesive film that the adhesive film can exhibit high bendability, sufficient adhesion to an adherend, and high cohesive force of the acrylic adhesive; the acrylic pressure-sensitive adhesive composition may constitute the acrylic pressure-sensitive adhesive described above. An adhesive film according to an embodiment of the present invention is an adhesive film comprising an adhesive layer comprising an acrylic adhesive, the adhesive force of the acrylic adhesive to a polyimide film measured at 23 DEG C at a peeling speed of 10 mm / min and a peeling angle of 180 degrees being 700 gf / 25 mm or more, the adhesive force of the acrylic adhesive to a polyimide film measured at a peeling speed of 6000 mm / min and a peeling angle of 180 degrees at 23 DEG C is 1300 gf / 25 mm or more, and the storage modulus of the acrylic adhesive at-20 DEG C is less than 140 kPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive film, an acrylic adhesive composition and a flexible device. Background Art

[0002] Adhesive films are used for reinforcement and surface protection of components of various shapes.

[0003] For example, when an integrated circuit (IC) or a flexible printed circuit board (FPC) is joined to a substrate of a semiconductor element (e.g., a TFT substrate, etc.), thermocompression bonding is usually performed via an anisotropic conductive film (ACF). When performing such thermocompression bonding, an adhesive film is sometimes laminated to the back side of the substrate of the semiconductor element in advance for reinforcement (e.g., Patent Document 1).

[0004] In addition, in recent years, as a manufacturing method for so-called flexible devices such as foldable devices and rollable devices that are being developed, the following method is generally used: a peeling layer and a flexible film substrate are formed on a supporting substrate such as glass, a TFT substrate is formed on the film substrate, and an organic EL layer is further formed on the TFT substrate. Then, the supporting substrate is peeled off to manufacture a flexible device, but since the flexible display layer is very thin, the device may have a malfunction due to handling, etc. Therefore, an adhesive film is sometimes attached to the back side in advance for reinforcement (for example, Patent Document 2).

[0005] Semiconductor element substrates and flexible devices are sometimes bent repeatedly. If the adhesive film attached to the substrate has poor bending properties, the recovery after bending will deteriorate or, in the worst case, the film will break due to repeated bending.

[0006] In order to make the adhesive film have good flexibility, the adhesive of the adhesive film is required to have a low elastic modulus. Generally, the elastic modulus in the low temperature region is higher than the elastic modulus in the normal temperature region. Therefore, it is particularly required to have a low elastic modulus in the low temperature region.

[0007] However, there have been problems in the past: if the elastic modulus of the adhesive is reduced in a low temperature region, the adhesion between the adhesive and the adherend is reduced, or the cohesive force of the adhesive is weakened. If such a problem occurs, the adhesive film cannot withstand the stress during bending.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5600039

[0011] Patent Document 2: Japanese Patent No. 6376271 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The problem of the present invention is to provide an adhesive film, the adhesive film includes an adhesive layer composed of an acrylic adhesive, which can take into account high flexibility, sufficient adhesion to an adherend, and high cohesion of the acrylic adhesive. The problem of the present invention is also to provide an acrylic adhesive composition, the acrylic adhesive composition can constitute an acrylic adhesive that can take into account high flexibility, sufficient adhesion to an adherend, and high cohesion. The problem of the present invention is to provide a flexible device, the flexible device having such an adhesive film.

[0014] Solutions for solving problems

[0015] [1] The adhesive film of an embodiment of the present invention is an adhesive film comprising an adhesive layer composed of an acrylic adhesive, wherein the adhesive strength of the acrylic adhesive to a polyimide film measured at a peeling rate of 10 mm / min and a peeling angle of 180 degrees at 23°C is 700 gf / 25 mm or more, and the adhesive strength of the acrylic adhesive to a polyimide film measured at a peeling rate of 6000 mm / min and a peeling angle of 180 degrees at 23°C is 1300 gf / 25 mm or more, and the storage modulus of the acrylic adhesive at -20°C is less than 140 kPa.

[0016] [2] In the adhesive film according to [1] above, the shear retention rate of the acrylic adhesive may be 50% or more.

[0017] [3] In the adhesive film according to [1] or [2] above, the acrylic adhesive may have a creep value of 45% or more at -20°C.

[0018] [4] The acrylic pressure-sensitive adhesive composition according to an embodiment of the present invention is an acrylic pressure-sensitive adhesive composition that forms an acrylic pressure-sensitive adhesive, and the acrylic pressure-sensitive adhesive composition contains an acrylic polymer, an acrylic oligomer, and two or more cross-linking agents.

[0019] [5] In the acrylic pressure-sensitive adhesive composition according to [4] above, the two or more cross-linking agents may include an epoxy cross-linking agent.

[0020] [6] In the acrylic pressure-sensitive adhesive composition according to [5] above, the two or more cross-linking agents may include both an epoxy cross-linking agent and an isocyanate cross-linking agent.

[0021] [7] In the acrylic pressure-sensitive adhesive composition according to [5] or [6] above, the content of the epoxy crosslinking agent may be 0.05 parts by weight or more based on 100 parts by weight of the acrylic polymer.

[0022] [8] In the acrylic pressure-sensitive adhesive composition according to any one of [4] to [7] above, the content of the acrylic oligomer may be 5 parts by weight or more relative to 100 parts by weight of the acrylic polymer.

[0023] [9] In the acrylic pressure-sensitive adhesive composition according to any one of [4] to [8] above, the acrylic oligomer may be a carboxyl group-containing acrylic oligomer.

[0024]

[10] In the acrylic pressure-sensitive adhesive composition according to any one of [4] to [9] above, the acrylic polymer may be a hydroxyl group-containing acrylic polymer.

[0025]

[11] A flexible device according to an embodiment of the present invention comprises the adhesive film according to any one of [1] to [3] above.

[0026] Effects of the Invention

[0027] According to the present invention, there is provided an adhesive film, which includes an adhesive layer composed of an acrylic adhesive, and which can take into account high flexibility, sufficient adhesion to an adherend, and high cohesion of the acrylic adhesive. According to the present invention, there is also provided an acrylic adhesive composition, which can constitute an acrylic adhesive that can take into account high flexibility, sufficient adhesion to an adherend, and high cohesion. According to the present invention, there is further provided a flexible device having such an adhesive film. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic cross-sectional view showing one embodiment of the flexible device of the present invention, and shows one mode of use of the adhesive film of the embodiment of the present invention. DETAILED DESCRIPTION

[0029] In the present specification, "(meth)acrylic acid" means "acrylic acid and / or methacrylic acid", "(meth)acrylate" means "acrylate and / or methacrylate", "(meth)allyl" means "allyl and / or methallyl", and "(meth)acrolein" means "acrolein and / or methacrolein". In addition, in the present specification, "acid (salt)" means "acid and / or its salt". Examples of the salt include alkali metal salts and alkaline earth metal salts, and specifically, examples include sodium salts and potassium salts.

[0030] 《《1. Adhesive film》》

[0031] The pressure-sensitive adhesive film according to the embodiment of the present invention includes a pressure-sensitive adhesive layer composed of an acrylic pressure-sensitive adhesive.

[0032] The adhesive film of the embodiment of the present invention may be a substrate-free film consisting only of an adhesive layer, or may be a substrate-attached film having a substrate layer and an adhesive layer. The adhesive film of the present invention may also include any appropriate other layers in addition to the substrate layer and the adhesive layer, within the range that does not impair the effects of the present invention.

[0033] The substrate layer may be a single layer or may be two or more layers. From the viewpoint of better expressing the effects of the present invention, the substrate layer is preferably a single layer.

[0034] The adhesive layer may be a single layer or may be two or more layers. From the viewpoint of better exhibiting the effects of the present invention, the adhesive layer is preferably a single layer.

[0035] The pressure-sensitive adhesive film according to the embodiment of the present invention may include any appropriate release liner on the surface of the pressure-sensitive adhesive layer opposite to the surface on which the substrate layer is provided, for the purpose of protection before use or the like.

[0036] Examples of release liners include release liners in which the surface of a substrate (lining substrate) such as paper or plastic film is treated with silicone, and release liners in which the surface of a substrate (lining substrate) such as paper or plastic film is laminated with a polyolefin resin. Examples of plastic films used as lining substrates include polyethylene films, polypropylene films, polybutylene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.

[0037] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, further preferably 5 μm to 400 μm, and particularly preferably 10 μm to 300 μm.

[0038] The total thickness of the adhesive film of the embodiment of the present invention is preferably 1 μm to 500 μm, more preferably 5 μm to 200 μm, further preferably 10 μm to 150 μm, particularly preferably 20 μm to 100 μm, and most preferably 30 μm to 80 μm. If the thickness of the adhesive film of the embodiment of the present invention is within the above range, the effect of the present invention can be more effectively exhibited.

[0039] 《1-1. Base material layer》

[0040] The thickness of the substrate layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, further preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm. If the thickness of the substrate layer is within the above range, the effect of the present invention can be more effectively exhibited.

[0041] As the material of the base layer, any appropriate material can be adopted within the range not impairing the effect of the present invention. As the material of such a base layer, a resin material can be typically mentioned.

[0042] Examples of resin materials used as the substrate layer include acrylic resins such as polyimide (PI), polyetheretherketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA); polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resins, and cyclic olefin polymers.

[0043] 《1-2. Adhesive layer》

[0044] The thickness of the adhesive layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, further preferably 10 μm to 100 μm, particularly preferably 10 μm to 80 μm, and most preferably 10 μm to 60 μm. If the thickness of the adhesive layer is within the above range, the effect of the present invention can be more effectively exhibited.

[0045] The adhesive layer is composed of an acrylic adhesive. More specifically, the adhesive layer is formed by making an acrylic adhesive into a layer shape. As a method for forming the adhesive layer, any appropriate method of formation can be adopted within the scope that does not damage the effect of the present invention. As such a formation method, for example, the following method can be cited: an acrylic adhesive composition is applied to any appropriate substrate, heated / dried as needed, and cured as needed to form an adhesive layer composed of an acrylic adhesive on the substrate. As such a coating means, any appropriate means can be adopted within the scope that does not damage the effect of the present invention. As such a coating means, for example, gravure roll coater, reverse roll coater, contact roll coater, immersion roll coater, scraper bar coater, scraper coater, air knife coater, sprayer, comma scraper coater, direct coater, roller brush coater. The heating / drying of the acrylic adhesive composition can adopt any appropriate means within the scope that does not damage the effect of the present invention. As such a heating / drying means, for example, heating to about 60°C to 180°C can be cited. The acrylic adhesive composition may be cured by any appropriate means within the range not impairing the effects of the present invention, such as ultraviolet irradiation, laser irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.

[0046] <1-2-1. Acrylic adhesive>

[0047] In the adhesive film of the embodiment of the present invention, the adhesive force of the acrylic adhesive to the polyimide film measured at a peeling speed of 10 mm / min and a peeling angle of 180 degrees at 23°C is preferably 700 gf / 25 mm or more, more preferably 800 gf / 25 mm or more, further preferably 850 gf / 25 mm or more, and particularly preferably 900 gf / 25 mm or more. The larger the upper limit of the above-mentioned adhesive force, the better, but in reality it is preferably 3000 gf / 25 mm or less. The larger the measured value of the adhesive force of the acrylic adhesive to the polyimide film measured at a peeling speed of 10 mm / min and a peeling angle of 180 degrees at 23°C, the higher the adhesion of the acrylic adhesive to the adherend. The reason is that since the peeling speed is slower at 10 mm / min, the cohesive force of the acrylic adhesive in the measurement becomes smaller, and the adhesion at the interface of the acrylic adhesive and the adherend is reflected in the measured value to a large extent. Therefore, in the adhesive film of the embodiment of the present invention, if the adhesive strength of the acrylic adhesive to the polyimide film measured at 23° C. at a peeling rate of 10 mm / min and a peeling angle of 180 degrees is within the above range, the acrylic adhesive can exhibit sufficient adhesion to the adherend. The method for measuring the above adhesive strength will be described in detail later.

[0048] In the adhesive film of the embodiment of the present invention, the adhesive force of the acrylic adhesive to the polyimide film measured at a peeling speed of 6000mm / min and a peeling angle of 180 degrees at 23°C is preferably 1300gf / 25mm or more, more preferably 1350gf / 25mm or more, further preferably 1400gf / 25mm or more, particularly preferably 1450gf / 25mm or more, and most preferably 1500gf / 25mm or more. The larger the upper limit of the above-mentioned adhesive force, the better, but in reality, it is preferably 2500gf / 25mm or less. The larger the measured value of the adhesive force of the acrylic adhesive to the polyimide film measured at a peeling speed of 6000mm / min and a peeling angle of 180 degrees at 23°C, the higher the cohesive force of the acrylic adhesive. The reason is that, since the peeling speed is faster at 6000mm / min, the adhesion between the acrylic adhesive and the adherend interface in the measurement becomes smaller, and the cohesive force of the acrylic adhesive is reflected in the measured value to a greater extent. Therefore, in the adhesive film of the embodiment of the present invention, if the adhesive strength of the acrylic adhesive to the polyimide film measured at 23° C. at a peeling rate of 6000 mm / min and a peeling angle of 180 degrees is within the above range, the acrylic adhesive can exhibit high cohesive strength. The method for measuring the above adhesive strength will be described in detail later.

[0049] In the adhesive film of the embodiment of the present invention, the storage modulus of the acrylic adhesive at -20°C is preferably less than 140 kPa, more preferably less than 135 kPa, further preferably less than 130 kPa, particularly preferably less than 125 kPa, and most preferably less than 120 kPa. From the viewpoint of operability, the lower limit of the above storage modulus is preferably 30 kPa or more in reality. In the adhesive film of the embodiment of the present invention, if the storage modulus of the acrylic adhesive at -20°C is within the above range, the acrylic adhesive can exhibit high flexibility due to the low elastic modulus in the low temperature region. The method for measuring the storage modulus of the acrylic adhesive at -20°C will be described in detail later.

[0050] In the adhesive film of the embodiment of the present invention, the shear retention rate of the acrylic adhesive is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 74% or more, and most preferably 78% or more. The upper limit of the above shear retention rate is 100% or less in reality. Acrylic adhesives are subjected to stress in the shear direction when bent, so the higher the shear retention rate of the acrylic adhesive, the higher the peeling resistance when bent. If the above shear retention rate is low, the acrylic adhesive may be peeled off from the adherend and cohesive failure in the acrylic adhesive may occur when bent. The method for measuring the shear retention rate will be described in detail later.

[0051] In the adhesive film of the embodiment of the present invention, the creep value of the acrylic adhesive at -20°C is preferably 45% or more, more preferably 47% or more, further preferably 49% or more, and particularly preferably 50% or more. The upper limit of the above creep value is generally the larger the better, but if the balance with other adhesive properties is taken into account, it is preferably 200% or less. The creep value at -20°C is an indicator of the stress relaxation property for bending action in a low temperature environment. The larger the creep value at -20°C, the better the stress relaxation property for bending action in a low temperature environment. If the creep value of the above acrylic adhesive at -20°C is low, the stress relaxation property for bending action in a low temperature environment becomes low, which may cause cracks, fractures, etc. in surrounding components during bending. The method for measuring the creep value of the acrylic adhesive at -20°C will be described in detail later.

[0052] In the adhesive film of the embodiment of the present invention, it is more preferred that all of the following (1), (2), and (3) are adjusted to the above-mentioned preferred range: (1) the adhesive strength of the acrylic adhesive to the polyimide film measured at a peeling speed of 10 mm / min and a peeling angle of 180 degrees at 23°C; (2) the adhesive strength of the acrylic adhesive to the polyimide film measured at a peeling speed of 6000 mm / min and a peeling angle of 180 degrees at 23°C; and (3) the storage modulus of the acrylic adhesive at -20°C. By adjusting in this way, an adhesive film can be obtained that can take into account high flexibility, sufficient adhesion to the adherend, and high cohesion of the acrylic adhesive. As mentioned above, in the past, in the design of adhesives that can exhibit flexibility, the elastic modulus of the adhesive in the low temperature region and the adhesion of the adhesive to the adherend and the cohesion of the adhesive are in a compromise relationship. The adhesive film according to the embodiment of the present invention can satisfactorily balance the elastic modulus of the adhesive in a low temperature range, the adhesion between the adhesive and the adherend, and the cohesive force of the adhesive, which have been in a trade-off relationship in the past.

[0053] In the adhesive film of the embodiment of the present invention, from the viewpoint of being able to exhibit better flexibility, etc., it is further preferred that all of the above-mentioned (1), (2), and (3) of the acrylic adhesive are adjusted to be within the above-mentioned preferred range, and further at least one of the group consisting of the following (4) and (5) selected from the above-mentioned is adjusted to be within the above-mentioned preferred range: (4) the shear retention rate of the acrylic adhesive; and (5) the creep value of the acrylic adhesive at -20°C.

[0054] In the adhesive film according to the embodiment of the present invention, the acrylic adhesive is preferably formed of an acrylic adhesive composition.

[0055] The acrylic adhesive can be defined as a substance formed of an acrylic adhesive composition. The reason for this is that, in the case of an acrylic adhesive, the acrylic adhesive composition undergoes a crosslinking reaction by heating, ultraviolet irradiation, etc. to become an acrylic adhesive, so it is impossible and completely impractical to directly specify the acrylic adhesive by its structure. Due to the above situation ("impossible and impractical situation"), the acrylic adhesive is appropriately specified as a "substance" by defining it as a "substance formed of an acrylic adhesive composition".

[0056] In the case where the acrylic adhesive is formed by an acrylic adhesive composition, any appropriate method can be used as a method for forming the acrylic adhesive within the scope of not damaging the effect of the present invention. As a method for forming such an acrylic adhesive, for example, the following method can be cited: the acrylic adhesive composition is applied to any appropriate substrate, heated / dried as needed, and cured as needed to form an acrylic adhesive on the substrate. As such a coating means, any appropriate means can be used within the scope of not damaging the effect of the present invention. As such a coating means, for example, a gravure roll coater, a reverse roll coater, a contact roll coater, an immersion roll coater, a scraper bar coater, a scraper coater, an air knife coater, a sprayer, a comma scraper coater, a direct coater, and a roller brush coater. The heating / drying of the acrylic adhesive composition can be carried out by any appropriate means within the scope of not damaging the effect of the present invention. As such a heating / drying means, for example, heating to about 60°C to 180°C can be cited. The acrylic adhesive composition may be cured by any appropriate means within the range not impairing the effects of the present invention, such as ultraviolet irradiation, laser irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.

[0057] The adhesive film of the embodiment of the present invention comprises an adhesive layer composed of an acrylic adhesive, and the acrylic adhesive is preferably formed of an acrylic adhesive composition as described above. Such an acrylic adhesive composition can adopt any appropriate acrylic adhesive composition within the range that does not impair the effect of the present invention. As such an acrylic adhesive composition, from the viewpoint of being able to better demonstrate the effect of the present invention, the acrylic adhesive composition of the embodiment of the present invention described below can be preferably adopted.

[0058] 《《2. Acrylic adhesive composition》》

[0059] The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention is an acrylic pressure-sensitive adhesive composition that forms an acrylic pressure-sensitive adhesive.

[0060] The acrylic adhesive composition of the embodiment of the present invention comprises an acrylic polymer, an acrylic oligomer, and two or more crosslinking agents. The acrylic adhesive composition of the embodiment of the present invention comprises an acrylic oligomer in addition to the acrylic polymer as a base polymer, and further comprises two or more crosslinking agents in combination, thereby effectively expressing the effect of the present invention. If the acrylic adhesive composition of the embodiment of the present invention does not contain an acrylic oligomer, or only comprises one crosslinking agent, the effect of the present invention may not be expressed.

[0061] From the perspective of better demonstrating the effects of the present invention, the content of the acrylic polymer in the acrylic adhesive composition of the embodiment of the present invention is preferably 50% by weight or more, more preferably 70% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably 97% by weight or more. The upper limit of the above content is preferably 100% by weight or less.

[0062] In the acrylic adhesive composition of the embodiment of the present invention, the content of acrylic oligomer is preferably 5 weight parts or more relative to 100 weight parts of acrylic polymer, more preferably 5 weight parts or more and less than 16 weight parts, further preferably 6 weight parts or more and less than 15 weight parts, particularly preferably 7 weight parts or more and less than 14 weight parts, most preferably 8 weight parts or more and less than 13 weight parts. If the content of acrylic oligomer is within the above range, the effect of the present invention can be more shown. If the content of acrylic oligomer is too little, the effect of the present invention may not be shown, for example, the adhesion of acrylic adhesive to adherend may be reduced. If the content of acrylic oligomer is too much, the effect of the present invention may not be shown, for example, the elastic modulus in the low temperature region may become high.

[0063] In the acrylic adhesive composition of the embodiment of the present invention, the total amount of the two or more cross-linking agents is preferably 0.05 parts by weight or more, more preferably 0.10 parts by weight or more and less than 3.00 parts by weight, further preferably 0.15 parts by weight or more and less than 2.50 parts by weight, further preferably 0.20 parts by weight or more and less than 2.00 parts by weight, further preferably 0.25 parts by weight or more and less than 1.50 parts by weight, further preferably 0.30 parts by weight or more and less than 1.50 parts by weight, further preferably 0.35 parts by weight or more and less than 1.40 parts by weight, particularly preferably 0.40 parts by weight or more and less than 1.30 parts by weight, and most preferably 0.45 parts by weight or more and less than 1.20 parts by weight.

[0064] 《2-1. Acrylic polymers》

[0065] The acrylic polymer may be used alone or in combination of two or more.

[0066] The weight average molecular weight Mw of the acrylic polymer is preferably 2.5 million or less, more preferably 2.4 million or less, further preferably 2.3 million or less, further preferably 2.2 million or less, and particularly preferably 2.1 million or less. The lower limit of the weight average molecular weight Mw is preferably 1 million or more. The method for measuring the weight average molecular weight Mw will be described in detail later.

[0067] From the viewpoint of further expressing the effects of the present invention, the acrylic polymer is preferably a hydroxyl group-containing acrylic polymer.

[0068] The acrylic polymer can be obtained by polymerizing the monomer component (M).

[0069] The acrylic polymer can be defined as a substance obtained by polymerizing the monomer component (M). The reason is that, in the case of an acrylic polymer, the monomer component (M) undergoes a polymerization reaction to become an acrylic polymer, and it is impossible and completely impractical to directly specify the acrylic polymer by its structure. Due to the above situation ("impossible and impractical situation"), the acrylic polymer is appropriately specified as a "substance" by defining it as "a substance obtained by polymerizing the monomer component (M)".

[0070] The monomer component (M) preferably contains an alkyl (meth)acrylate. The alkyl group of the ester part is preferably an alkyl group having 1 to 16 carbon atoms. The alkyl group of the ester part referred to here does not include an alkyl group containing a polar group such as a hydroxyl group. The alkyl (meth)acrylate may be only one type or two or more types.

[0071] From the viewpoint of better expressing the effects of the present invention, the content of the alkyl (meth)acrylate in the monomer component (M) is preferably 50% to 99% by weight, more preferably 70% to 99% by weight, further preferably 80% to 99% by weight, further preferably 90% to 99% by weight, particularly preferably 95% to 99% by weight, and most preferably 97% to 99% by weight. If the content of the alkyl (meth)acrylate in the monomer component (M) is within the above range, the effects of the present invention can be better expressed.

[0072] As the alkyl (meth)acrylate, any appropriate alkyl (meth)acrylate can be adopted within the range not impairing the effects of the present invention. As such an alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be preferably used.

[0073] CH2=C(R 1 )COOR 2(1)

[0074] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group, R 2 It is an alkyl group having 1 to 20 carbon atoms.

[0075] From the perspective of better demonstrating the effect of the present invention, R 2 An alkyl group having 1 to 16 carbon atoms is preferred, an alkyl group having 2 to 14 carbon atoms is more preferred, an alkyl group having 4 to 14 carbon atoms is further preferred, and an alkyl group having 4 to 12 carbon atoms is particularly preferred.

[0076] From the viewpoint of better expressing the effects of the present invention, the alkyl group is preferably a chain alkyl group. Here, the chain alkyl group includes a straight chain alkyl group and a branched chain alkyl group.

[0077] As R 2 Examples of the alkyl (meth)acrylates having a linear alkyl group having 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate.

[0078] From the perspective of better expressing the effect of the present invention, the glass transition temperature Tg of the homopolymer (homopolymer) of the (meth)acrylic acid alkyl ester that can be included in the monomer component (M) is preferably below -10°C, more preferably below -12°C, further preferably below -15°C, particularly preferably below -18°C, and most preferably below -20°C. The lower limit of the above-mentioned glass transition temperature Tg is preferably above -80°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the (meth)acrylic acid alkyl ester that can be included in the monomer component (M) may affect the adhesive properties and bending properties of the acrylic polymer. As the (meth)acrylic acid alkyl ester that can be included in the monomer component (M), an (meth)acrylic acid alkyl ester whose homopolymer (homopolymer) has a glass transition temperature Tg within the above-mentioned range is used, thereby appropriately adjusting the adhesive properties and bending properties of the acrylic polymer, and better expressing the effect of the present invention.

[0079] Here, as the glass transition temperature Tg of the homopolymer of the (meth)acrylic acid alkyl ester that may be included in the monomer component (M), the value recorded in the known data can be used, for example, the value recorded in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. It should be noted that when multiple values ​​are recorded in the above-mentioned "Polymer Handbook", the conventional value is adopted. For the (meth)acrylic acid alkyl ester not recorded in the above-mentioned "Polymer Handbook", the catalog value of the monomer manufacturer is adopted. As the Tg of the homopolymer of the (meth)acrylic acid alkyl ester not recorded in the above-mentioned "Polymer Handbook" and the catalog value of the monomer manufacturer is not provided, the value obtained by the measurement method described in Japanese Patent Gazette No. 2007-51271 is used.

[0080] Typical examples of the glass transition temperature Tg of the homopolymer of the (meth)acrylic acid alkyl ester which may be contained in the monomer component (M) are as follows.

[0081] 2-Ethylhexyl acrylate (2EHA): -70°C.

[0082] Lauryl acrylate (LA): -23°C.

[0083] n-Butyl acrylate (BA): -55°C.

[0084] From the viewpoint of better expressing the effect of the present invention, the monomer component (M) preferably contains, as the (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester (m1) whose homopolymer has a glass transition temperature Tg in the range of -80°C to -60°C. When the monomer component (M) contains the (meth)acrylic acid alkyl ester (m1), from the viewpoint of better expressing the effect of the present invention, the content ratio of the (meth)acrylic acid alkyl ester (m1) in the monomer component (M) is preferably 40% by weight to 99% by weight, more preferably 50% by weight to 90% by weight, further preferably 55% by weight to 85% by weight, particularly preferably 60% by weight to 80% by weight, and most preferably 65% ​​by weight to 75% by weight.

[0085] As an example of the (meth)acrylic acid alkyl ester (m1), 2-ethylhexyl acrylate (2EHA) (the glass transition temperature of the homopolymer thereof (homopolymer) is Tg=-70°C) is mentioned.

[0086] From the perspective of being able to better express the effects of the present invention, the monomer component (M) preferably contains, as the (meth)acrylic acid alkyl ester, an (meth)acrylic acid alkyl ester (m2) whose homopolymer has a glass transition temperature Tg in the range of -40°C to -10°C. When the monomer component (M) contains the (meth)acrylic acid alkyl ester (m2), from the perspective of being able to better express the effects of the present invention, the content of the (meth)acrylic acid alkyl ester (m2) in the monomer component (M) is preferably 1% by weight to 50% by weight, more preferably 3% by weight to 30% by weight, further preferably 4% by weight to 20% by weight, particularly preferably 5% by weight to 15% by weight, and most preferably 6% by weight to 10% by weight.

[0087] As an example of the (meth)acrylic acid alkyl ester (m2), lauryl acrylate (LA) (the glass transition temperature of the homopolymer (homopolymer) is Tg=-23°C) is mentioned.

[0088] From the perspective of better expressing the effects of the present invention, the monomer component (M) preferably contains, as the (meth)acrylic acid alkyl ester, an (meth)acrylic acid alkyl ester (m3) whose homopolymer has a glass transition temperature Tg of more than -60°C and less than -40°C. When the monomer component (M) contains the (meth)acrylic acid alkyl ester (m3), from the perspective of better expressing the effects of the present invention, the content of the (meth)acrylic acid alkyl ester (m3) in the monomer component (M) is preferably 1% by weight to 45% by weight, more preferably 3% by weight to 40% by weight, further preferably 5% by weight to 35% by weight, particularly preferably 10% by weight to 30% by weight, and most preferably 15% by weight to 25% by weight.

[0089] As an example of the (meth)acrylic acid alkyl ester (m3), n-butyl acrylate (BA) (the glass transition temperature of the homopolymer (homopolymer) is Tg=-55°C) is mentioned.

[0090] From the viewpoint of further expressing the effects of the present invention, the monomer component (M) preferably contains at least one selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3), more preferably contains at least two selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3), and further preferably contains all of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3).

[0091] From the perspective of more effectively expressing the effects of the present invention, the monomer component (M) typically preferably contains at least one selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, more preferably contains at least two selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and further preferably contains all of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate.

[0092] The monomer component (M) preferably contains a hydroxyl group-containing monomer (m4). The hydroxyl group-containing monomer (m4) may be one kind or two or more kinds.

[0093] From the perspective of better expressing the effect of the present invention, the glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl-containing monomer (m4) that can be included in the monomer component (M) is preferably below -10°C, more preferably below -15°C, further preferably below -20°C, particularly preferably below -25°C, and most preferably below -30°C. The lower limit of the above-mentioned glass transition temperature Tg is preferably above -80°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl-containing monomer (m4) that can be included in the monomer component (M) may affect the adhesive properties and bending properties of the acrylic polymer. As the hydroxyl-containing monomer (m4) that can be included in the monomer component (M), a hydroxyl-containing monomer (m4) whose homopolymer (homopolymer) has a glass transition temperature Tg within the above-mentioned range is used, thereby appropriately adjusting the adhesive properties and bending properties of the acrylic polymer, and better expressing the effect of the present invention.

[0094] Here, the glass transition temperature Tg of the homopolymer of the hydroxyl group-containing monomer (m4) which may be contained in the monomer component (M) may be determined in the same manner as the glass transition temperature Tg of the homopolymer of the above-mentioned (meth)acrylate.

[0095] Representative examples of the glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (m4) which may be contained in the monomer component (M) are as follows.

[0096] 2-Hydroxyethyl acrylate: -15°C.

[0097] 4-Hydroxybutyl acrylate: -40°C.

[0098] When the monomer component (M) contains a hydroxyl-containing monomer (m4), from the perspective of better expressing the effect of the present invention, the content of the hydroxyl-containing monomer (m4) in the monomer component (M) is preferably 0.01% by weight to 30% by weight, more preferably 0.05% by weight to 10% by weight, further preferably 0.1% by weight to 5.0% by weight, particularly preferably 0.3% by weight to 3.0% by weight, and most preferably 0.5% by weight to 1.5% by weight.

[0099] Examples of the hydroxyl group-containing monomer (m4) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl (meth)acrylamide.

[0100] From the perspective of being able to better express the effects of the present invention, the hydroxyl group-containing monomer (m4) preferably includes a hydroxyalkyl (meth)acrylate, and more preferably includes a hydroxyalkyl (meth)acrylate in which the alkyl portion is a linear alkyl group having 2 to 4 carbon atoms. Examples of the hydroxyalkyl (meth)acrylate include 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA), and from the perspective of being able to better express the effects of the present invention, 4-hydroxybutyl acrylate is preferred.

[0101] From the perspective of better expressing the effects of the present invention, the monomer component (M) preferably contains at least one selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3) and a hydroxyl-containing monomer (m4), more preferably contains at least two selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3) and a hydroxyl-containing monomer (m4), and further preferably contains all of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3) and a hydroxyl-containing monomer (m4).

[0102] From the perspective of better expressing the effects of the present invention, representatively, the monomer component (M) preferably contains at least one selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate and a hydroxyl-containing monomer (m4), more preferably contains at least two selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate and a hydroxyl-containing monomer (m4), and further preferably contains all of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate and a hydroxyl-containing monomer (m4).

[0103] The monomer component (M) may contain other monomers within a range that does not impair the effects of the present invention. Other monomers may be used, for example, for purposes such as adjusting the glass transition temperature (Tg) of the acrylic polymer and adjusting the adhesive properties. Other monomers may be only one or more.

[0104] Examples of other monomers include carboxyl group-containing monomers, nitrogen-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyano group-containing monomers, acid anhydride group-containing monomers, vinyl esters (e.g., vinyl acetate (VAc), vinyl propionate, vinyl laurate), aromatic vinyl compounds, amide group-containing monomers, epoxy group-containing monomers, (meth)acryloylmorpholine, and vinyl ethers.

[0105] Examples of the carboxyl group-containing monomer include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0106] Examples of the nitrogen-containing monomer include nitrogen-containing vinyl monomers such as N-vinyl-2-pyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinylazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinylcarboxylic acid amides, and N-vinylcaprolactam; and cyano group-containing acrylic monomers such as acrylonitrile and methacrylonitrile.

[0107] As the other monomer, N-vinyl-2-pyrrolidone is preferred because the effect of improving the adhesive strength due to the improvement of the cohesive force is high.

[0108] The content of other monomers in the monomer component (M) is preferably 0% to 20% by weight, more preferably 0% to 10% by weight, further preferably 0% to 5% by weight, particularly preferably 0% to 3% by weight, and most preferably 0% to 1% by weight.

[0109] As a method for obtaining an acrylic polymer, for example, various polymerization methods known as synthetic methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, etc., can be appropriately adopted. Among these polymerization methods, solution polymerization can be preferably used. As a monomer supply method when performing solution polymerization, a one-time charging method of supplying the total amount of monomer components at one time, a continuous supply (drip) method, a divided supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., preferably 20°C or more, more preferably 30°C or more, more preferably 40°C or more, preferably 170°C or less, more preferably 160°C or less, and more preferably 140°C or less. As a method for obtaining an acrylic polymer, active energy ray irradiation polymerization can be adopted: photopolymerization by irradiation with light such as UV (typically, carried out in the presence of a photopolymerization initiator); radiation polymerization by irradiation with radiation such as β rays and γ rays; etc.

[0110] The solvent (polymerization solvent) used for solution polymerization can be appropriately selected from any appropriate organic solvent, for example, aromatic compounds such as toluene (typically, aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane.

[0111] The initiator (polymerization initiator) used for the polymerization can be appropriately selected from any appropriate polymerization initiator according to the type of the polymerization method. The polymerization initiator may be only one kind or two or more kinds.

[0112] Examples of the polymerization initiator include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2 Azo initiators such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate ; Peroxide initiators such as di(2-ethylhexyl) peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, dibenzoyl peroxide, tert-butyl peroxyisobutyrate, 1,1-di(tert-hexylperoxy)cyclohexane, tert-butyl hydroperoxide, and hydrogen peroxide; Redox initiators formed by combining peroxides with reducing agents, such as a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate; Substituted ethane initiators such as phenyl-substituted ethane; Aromatic carbonyl compounds.

[0113] The amount of the polymerization initiator used may be any appropriate amount within the range not impairing the effects of the present invention, and is preferably 0.005 to 1 part by weight, more preferably 0.01 to 1 part by weight, relative to 100 parts by weight of the monomer component (M).

[0114] During the polymerization, any appropriate other additives may be contained within a range not impairing the effects of the present invention.

[0115] 《2-2. Acrylic oligomers》

[0116] The acrylic oligomer may be used alone or in combination of two or more.

[0117] The weight average molecular weight Mw of the acrylic oligomer is preferably 1000 to 30000, more preferably 1500 to 10000, further preferably 2000 to 8000, particularly preferably 2000 to 5000. By using an acrylic oligomer having such a weight average molecular weight Mw, the adhesive properties and bending properties of the acrylic pressure-sensitive adhesive can be improved.

[0118] The glass transition temperature Tg of the acrylic oligomer is preferably 20° C. or higher, more preferably 30° C. or higher, further preferably 40° C. or higher, particularly preferably 50° C. or higher, and most preferably 60° C. or higher. The upper limit of the glass transition temperature Tg of the acrylic oligomer is preferably 200° C. or lower, more preferably 180° C. or lower, and further preferably 160° C. or lower.

[0119] The glass transition temperature Tg of an acrylic oligomer refers to a value obtained by the Fox equation based on the Tg of a homopolymer of each monomer and the weight fraction (copolymerization ratio based on weight) of the monomer. As shown below, the Fox equation refers to the relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer formed by homopolymerizing the monomers constituting the copolymer.

[0120] 1 / Tg=Σ(Wi / Tgi)

[0121] In the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K). As the Tg of the homopolymer, the value recorded in the known data can be used, for example, the value recorded in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. In the case where multiple values ​​are recorded in the above "Polymer Handbook", the conventional value is adopted. For monomers not recorded in the above "Polymer Handbook", the catalog value of the monomer manufacturer is adopted. As the Tg of the homopolymer of the monomer not recorded in the above "Polymer Handbook" and the catalog value of the monomer manufacturer is not provided, the value obtained by the measurement method described in Japanese Patent Gazette No. 2007-51271 is used.

[0122] The acrylic oligomer contains an alicyclic alkyl (meth)acrylate as a main monomer component. The alicyclic alkyl (meth)acrylate may be one type or two or more types.

[0123] Examples of the alicyclic alkyl (meth)acrylate include cycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylates having a dicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylates having an aliphatic hydrocarbon ring having three or more rings such as dicyclopentyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, tricyclopentyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.

[0124] As the alicyclic alkyl (meth)acrylate, dicyclopentyl acrylate, dicyclopentyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred because the effects of the present invention can be more effectively exhibited.

[0125] From the viewpoint of better expressing the effects of the present invention, the content ratio of the alicyclic alkyl (meth)acrylate relative to the total amount of the monomer components constituting the acrylic oligomer is preferably 10% by weight to 99% by weight, more preferably 30% by weight to 99% by weight, further preferably 50% by weight to 98% by weight, particularly preferably 70% by weight to 98% by weight, and most preferably 90% by weight to 98% by weight.

[0126] From the viewpoint of more effectively expressing the effects of the present invention, the acrylic oligomer is preferably a carboxyl group-containing acrylic oligomer.

[0127] The carboxyl group-containing acrylic oligomer preferably contains (meth)acrylic acid as a constituent monomer component. As the (meth)acrylic acid, acrylic acid is preferred from the viewpoint that the effects of the present invention can be more effectively exhibited.

[0128] From the viewpoint of better expressing the effects of the present invention, the content ratio of (meth)acrylic acid relative to the total amount of monomer components constituting the acrylic oligomer is preferably 0.1 to 20% by weight, more preferably 1 to 10% by weight, further preferably 2 to 8% by weight, and particularly preferably 3 to 7% by weight.

[0129] The acrylic oligomer may contain a (meth) acrylic acid chain alkyl ester having a chain alkyl group as a constituent monomer component. The (meth) acrylic acid chain alkyl ester having a chain alkyl group may be only one type or may be two or more types. Here, chain refers to the meaning of including straight chain and branched chain.

[0130] The linear alkyl (meth)acrylate is preferably a linear alkyl (meth)acrylate having a linear alkyl group having 1 to 20 carbon atoms, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, Isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate.

[0131] From the viewpoint of further expressing the effects of the present invention, methyl methacrylate is preferred as the linear alkyl (meth)acrylate.

[0132] The content of the linear alkyl (meth)acrylate is preferably 70% by weight or less, more preferably 50% by weight or less, further preferably 30% by weight or less, particularly preferably 10% by weight or less, and most preferably 5% by weight or less based on the total amount of monomer components constituting the acrylic oligomer.

[0133] The acrylic oligomer is obtained by polymerizing the monomer components by various polymerization methods. When the polymerization is performed to obtain the acrylic oligomer, any appropriate additive can be used within the scope of not damaging the effect of the present invention. As such additives, for example, polymerization initiators and chain transfer agents can be listed.

[0134] 《2-3. Cross-linking agent》

[0135] The acrylic adhesive composition of the embodiment of the present invention contains two or more crosslinking agents as the crosslinking agent as described above. That is, the acrylic adhesive composition of the embodiment of the present invention contains two or more crosslinking agents as the crosslinking agent. If the acrylic adhesive composition of the embodiment of the present invention contains only one crosslinking agent, the effect of the present invention may not be exhibited.

[0136] The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains two or more crosslinking agents as described above, preferably two to five, more preferably two to four, further preferably two to three, and particularly preferably two.

[0137] As two or more crosslinking agents contained in the acrylic adhesive composition of the embodiment of the present invention, any appropriate crosslinking agent can be adopted within the range that does not impair the effect of the present invention. Such crosslinking agents include, for example, at least two crosslinking agents selected from the group consisting of epoxy crosslinking agents, isocyanate crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, and peroxides.

[0138] From the perspective of better demonstrating the effects of the present invention, the two or more crosslinking agents included in the acrylic adhesive composition of the embodiment of the present invention preferably include an epoxy crosslinking agent, and more preferably include both an epoxy crosslinking agent and an isocyanate crosslinking agent. The epoxy crosslinking agent may be only one or more than one. The isocyanate crosslinking agent may be only one or more than one.

[0139] In the case where the cross-linking agent includes an epoxy cross-linking agent, the content of the epoxy cross-linking agent is preferably 0.05 weight part or more relative to 100 weight parts of acrylic polymer, more preferably 0.05 weight part or more and less than 2 weight parts, further preferably 0.1 weight part or more and less than 1.5 weight parts, further preferably 0.2 weight part or more and less than 1.0 weight part, particularly preferably 0.3 weight part or more and less than 1.0 weight part, most preferably 0.4 weight part or more and less than 1.0 weight part. If the content of the epoxy cross-linking agent is within the above range, the effect of the present invention can be more manifested. If the content of the epoxy cross-linking agent is too little, the effect of the present invention may not be manifested, for example, the adhesion of the acrylic adhesive to the adherend may be reduced. If the content of the epoxy cross-linking agent is too much, the effect of the present invention may not be manifested, for example, the adhesion of the acrylic adhesive to the adherend may be reduced.

[0140] In the case where the crosslinking agent includes an epoxy crosslinking agent and an isocyanate crosslinking agent, the content of the isocyanate crosslinking agent relative to 100 parts by weight of the acrylic polymer is preferably 0.06 parts by weight or more, more preferably 0.06 parts by weight or more and less than 0.20 parts by weight, further preferably 0.07 parts by weight or more and less than 0.18 parts by weight, particularly preferably 0.07 parts by weight or more and less than 0.16 parts by weight, and most preferably 0.08 parts by weight or more and less than 0.15 parts by weight. If the content of the isocyanate crosslinking agent is within the above range, the effect of the present invention can be more clearly shown. If the content of the isocyanate crosslinking agent is too little, the effect of the present invention may not be shown, for example, the cohesive force of the acrylic adhesive may be reduced. If the content of the isocyanate crosslinking agent is too much, the effect of the present invention may not be shown, for example, the adhesion of the acrylic adhesive to the adherend may be reduced.

[0141] The crosslinking agent may be contained in the acrylic adhesive in a form after a crosslinking reaction, before a crosslinking reaction, partially crosslinked, or in an intermediate or composite form thereof. Typically, the crosslinking agent is contained in the acrylic adhesive in a form after a crosslinking reaction.

[0142] As the epoxy crosslinking agent, a polyfunctional epoxy compound having two or more epoxy groups in one molecule can be used. Examples of the epoxy crosslinking agent include: N, N, N', N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N, N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (polyglycerol polyglycidyl ether) ether), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol S diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Commercially available products of epoxy crosslinking agents include, for example, trade names "TETRAD C" and "TETRAD X" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0143] Isocyanate crosslinking agents may be compounds having two or more isocyanate groups (including isocyanate-regenerating polar groups whose isocyanate groups are temporarily protected by a blocking agent or polymerization) in one molecule. Examples of isocyanate crosslinking agents include aromatic isocyanates such as toluene diisocyanate and xylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.

[0144] Examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenyl isocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (e.g., manufactured by Tosoh, trade name CORONATE L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh, trade name CORONATE HL), isocyanurate of hexamethylene diisocyanate (e.g., manufactured by Tosoh, trade name CORONATE XT), and polyisocyanate derivatives thereof. isocyanate adducts such as trimethylolpropane adducts of xylylene diisocyanate (e.g., TAKENATE D110N, manufactured by Mitsui Chemicals, Inc.), trimethylolpropane adducts of xylylene diisocyanate (e.g., TAKENATE D120N, manufactured by Mitsui Chemicals, Inc.), trimethylolpropane adducts of isophorone diisocyanate (e.g., TAKENATE D140N, manufactured by Mitsui Chemicals, Inc.), and trimethylolpropane adducts of hexamethylene diisocyanate (e.g., TAKENATE D160N, manufactured by Mitsui Chemicals, Inc.); polyether polyisocyanates, polyester polyisocyanates, and adducts of these compounds with various polyols; polyisocyanates multifunctionalized by isocyanurate bonds, biuret bonds, allophanate bonds, etc. Among them, aromatic isocyanate and alicyclic isocyanate are preferred from the viewpoint of being able to achieve both deformability and cohesive force in a good balance.

[0145] 《2-4. Other ingredients》

[0146] The acrylic adhesive composition of the embodiment of the present invention may contain any appropriate other components within the range that does not impair the effect of the present invention. Such other components include, for example, polymer components other than acrylic polymers, crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, nucleating agents, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, anticorrosives, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.

[0147] 《《3. Flexible devices》》

[0148] The flexible device according to the embodiment of the present invention includes the adhesive film according to the embodiment of the present invention.

[0149] The adhesive film of the embodiment of the present invention can take into account high flexibility, sufficient adhesion to the adherend, and high cohesion of the acrylic adhesive. Therefore, it can be preferably set in flexible devices such as bendable devices (devices that can be bent) with movable bending parts, foldable devices (devices that can be folded), and rollable devices (devices that can be rolled up).

[0150] The flexible device of the present invention may include any appropriate other member as long as it includes the adhesive film according to the embodiment of the present invention.

[0151] Figure 1 This is a schematic cross-sectional view showing one embodiment of the flexible device of the present invention, and is a representative example of one usage form of the adhesive film according to the embodiment of the present invention. Figure 1 In the embodiment of the present invention, the flexible device 1000 includes: a cover film 10, an adhesive layer 20, a polarizer 30, an adhesive layer 40, a touch sensor 50, an adhesive layer 60, an OLED 70, and an adhesive film 100 according to the embodiment of the present invention. Figure 1 In the embodiment, the adhesive film 100 of the present invention is composed of an adhesive layer 80 and a base layer 90. The adhesive layer 20, the adhesive layer 40, and the adhesive layer 60 may be adhesive layers containing an adhesive having the same composition as the adhesive layer 80 constituting the adhesive film 100 of the present invention, or may be adhesive layers containing an adhesive having a composition different from that of the adhesive layer 80.

[0152] [Example]

[0153] The following examples and comparative examples are given to illustrate the present invention in more detail, but the present invention is not limited thereto. It should be noted that, in the following description, "parts" and "%" are by weight unless otherwise specified.

[0154] The abbreviations and details of raw materials and the like used in the following Production Examples, Examples, and Comparative Examples are as follows.

[0155] 2EHA: 2-ethylhexyl acrylate.

[0156] LA: Lauryl acrylate.

[0157] BA: n-butyl acrylate.

[0158] 4HBA: 4-Hydroxybutyl acrylate.

[0159] NVP: N-vinyl-2-pyrrolidone.

[0160] AIBN: 2,2'-azobisisobutyronitrile.

[0161] CHMA: cyclohexyl methacrylate.

[0162] AA: Acrylic acid.

[0163] C / HX: CORONATE HX (manufactured by Tosoh Corporation, an isocyanate-based crosslinking agent).

[0164] TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd., epoxy-based crosslinking agent).

[0165] Iron acetylacetonate: iron catalyst (manufactured by Nippon Chemical Industry Co., Ltd.).

[0166] <Adhesion to polyimide film at a peeling speed of 10 mm / min>

[0167] The adhesive film was cut into 25 mm width×100 mm length, the release liner was peeled off to expose the adhesive, and a polyimide film (trade name “UPILEX 50S”, manufactured by Ube Industries, Ltd.) was bonded to the film by reciprocating a 2 kg hand roller 1 to obtain an evaluation sample.

[0168] After the obtained evaluation sample was stored at room temperature for 30 minutes, it was measured with a tensile testing machine. As a tensile testing machine, the trade name "Autograph AG-Xplus HS 6000mm / min high-speed mode (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After assembling the evaluation sample in the tensile testing machine, the tensile test was started. The conditions of the tensile test were set as follows: the peeling angle was 180 degrees and the peeling speed (tensile speed) was 10mm / minute. The load when peeling the adhesive film from the above-mentioned polyimide film (UPILEX 50S) was measured, and the average load at this time was taken as the adhesive force.

[0169] <Adhesion to polyimide film at a peeling speed of 6000 mm / min>

[0170] The adhesive film was cut into 25 mm width×100 mm length, the release liner was peeled off to expose the adhesive, and a polyimide film (trade name “UPILEX 50S”, manufactured by Ube Industries, Ltd.) was bonded to the film by reciprocating a 2 kg hand roller 1 to obtain an evaluation sample.

[0171] After the obtained evaluation sample was stored at room temperature for 30 minutes, it was measured with a tensile testing machine. As a tensile testing machine, the trade name "Autograph AG-Xplus HS 6000mm / min high-speed mode (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After assembling the evaluation sample in the tensile testing machine, the tensile test was started. The conditions of the tensile test were set as follows: the peeling angle was 180 degrees and the peeling speed (tensile speed) was 6000mm / minute. The load when peeling the adhesive film from the above-mentioned polyimide film (UPILEX 50S) was measured, and the average load at this time was taken as the adhesive force.

[0172] <Preparation of test pieces for measuring storage modulus at -20°C and creep value at -20°C>

[0173] The coating solution of the acrylic adhesive composition was applied to a release sheet (Mitsubishi Chemical, MRV50T100J) of a polyester resin having a thickness of 50 μm and subjected to silicone treatment on one side, and dried at a drying temperature of 135° C. and a drying time of 1 minute. Next, the silicone-treated surface of a release sheet (Mitsubishi Chemical, MRQ50T100J) of a polyester resin having a thickness of 50 μm and subjected to silicone treatment on one side was bonded to the surface of the obtained adhesive layer in a contacting manner to prepare an adhesive film. The film was aged at 50° C. for one day to prepare a test piece.

[0174] <Storage modulus at -20℃>

[0175] Only the adhesive layer was taken out from the test piece, and the layer was laminated to a thickness of about 1 mm, and the layer was punched out to φ8 mm to prepare cylindrical pellets as measurement samples.

[0176] The obtained measurement sample was fixed to a jig of φ8 mm parallel plates using a dynamic viscoelasticity measuring apparatus (manufactured by TA Instruments, DHR-2), and the storage modulus was calculated. The measurement conditions were as follows.

[0177] Determination: Shear mode.

[0178] Temperature range: -50℃~200℃.

[0179] Heating rate: 5°C / min.

[0180] Frequency: 1Hz.

[0181] Strain: 0.1%.

[0182] <Creep value at -20℃>

[0183] Only the adhesive layer was taken out from the test piece, and the layer was laminated to a thickness of about 1 mm, and the layer was punched out to φ8 mm to prepare cylindrical pellets as measurement samples.

[0184] The obtained measurement sample was fixed to a jig of φ8 mm parallel plates using a dynamic viscoelasticity measuring apparatus (TA Instruments, DHR-2). A deformation stress of 10 kPa was applied at -20°C, and the deformation strain (%) after maintaining for 600 seconds was taken as the creep value at -20°C.

[0185] <Shear retention rate>

[0186] A polyimide film (trade name "UPILEX 50S", manufactured by Ube Industries) was bonded to an acrylic plate using a double-sided tape (manufactured by Nitto Denko Corporation, No. 500). The adhesive film was cut into a size of 25 mm in width and 100 mm in length, and the release liner was peeled off to expose the adhesive, and the film was bonded to the surface of the polyimide film bonded to the acrylic plate using a hand roller so that the bonding surface size was 25 mm × 25 mm, thereby obtaining a sample for evaluation.

[0187] The obtained evaluation sample was subjected to autoclave treatment under the conditions of 50°C, 0.5 MPa, and 15 minutes, and then measured using a tensile testing machine. As a tensile testing machine, the "Autograph AG-Xplus 5kN" manufactured by Shimadzu Corporation was used. After assembling the evaluation sample in the tensile testing machine, it was stretched 0.5 mm in the shear direction at a speed of 10 mm / min and maintained for 30 minutes. The maximum test force (F0) and the test force (F1) after 30 minutes were recorded, and the shear retention rate was calculated using Formula 1.

[0188] (Formula 1) F1×100 / F0

[0189] <Weight average molecular weight Mw>

[0190] The weight average molecular weight is measured by gel permeation chromatography (GPC). Specifically, as a GPC measuring device, "Agilent 1260 Infinity" (manufactured by Agilent Technologies Co., Ltd.) is used. Considering the polymer concentration of the sample, a 0.1 wt% tetrahydrofuran solution with an amine component added is prepared, left for 20 hours, filtered with a 0.45 μm membrane filter, and the resulting filtrate is subjected to GPC measurement. The following conditions are used for measurement and the standard polystyrene conversion value is calculated.

[0191] (Molecular weight measurement conditions)

[0192] Sample concentration: 0.1 wt% (tetrahydrofuran solution with amine components added).

[0193] Injection volume: 100 μL.

[0194] · Chromatographic column: Trade name “TSKgel GMH-H(S)” (manufactured by Tosoh Corporation).

[0195] · Eluent: Tetrahydrofuran with added amine components.

[0196] Flow rate: 0.5 mL / min.

[0197] · Detector: Differential Refractometer (RI).

[0198] · Column temperature (measurement temperature): 40°C.

[0199] ·Standard sample: polystyrene (PS).

[0200] [Production Example 1] Production of acrylic acid-based polymer

[0201] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a cooler were added the following: 70 parts by weight of 2EHA, 8 parts by weight of LA, 20 parts by weight of BA, 1 part by weight of 4HBA, 0.6 parts by weight of NVP, and 0.1 parts by weight of AIBN as a polymerization initiator. Ethyl acetate was added so that their total concentration became 47% by weight. The system was substituted with nitrogen for 1 hour while slowly stirring. The liquid temperature in the flask was maintained at approximately 56° C., and a polymerization reaction was carried out for 6 hours. After the reaction was completed, ethyl acetate was added to adjust the polymer concentration to 24% by weight, thereby obtaining a solution of an acrylic polymer.

[0202] [Production Example 2]: Production of acrylic acid oligomer

[0203] 95 parts by weight of CHMA and 5 parts by weight of AA were added as monomer components, 10 parts by weight of α-methylstyrene dimer (manufactured by NOF Corporation, trade name "Nofmer MSD") was added as a chain transfer agent, and 10 parts by weight of AIBN was added as a thermal polymerization initiator. Toluene was mixed in such a way that the concentration of these raw materials became 50% by weight, and the mixture was reacted at 85°C for 2 hours under a nitrogen atmosphere. Then, the temperature was raised to 86°C and reacted for 1.5 hours to obtain an acrylic oligomer. The weight average molecular weight Mw of the acrylic oligomer was 4000, and the glass transition temperature (Tg) was 67°C.

[0204] [Example 1]

[0205] 100 parts by weight of an acrylic polymer, 10 parts by weight of an acrylic oligomer, 0.1 parts by weight of C / HX as an isocyanate crosslinking agent, 0.5 parts by weight of TETRAD-C as an epoxy crosslinking agent, and 0.01 parts by weight of iron acetylacetonate as a catalyst were mixed and stirred thoroughly, and diluted with ethyl acetate and acetylacetone in an amount of 1% by weight of a solvent component so that the total solid content became 17% by weight, thereby obtaining a coating solution of an acrylic adhesive composition (1). The obtained coating solution of the acrylic adhesive composition (1) was applied to a polyester film (S-10#50 manufactured by Toray Co., Ltd.) so that the thickness after drying became 15 μm, and dried under the conditions of a drying temperature of 135° C. and a drying time of 1 minute. Next, a release sheet (Mitsubishi Chemical, product name: MRQ50T100J) having a thickness of 50 μm and having been subjected to silicone treatment on one side was bonded to the surface of the obtained adhesive layer with its silicone-treated surface in contact with the surface to obtain an adhesive film (1). The film was aged at 50° C. for one day and various evaluations were performed. The results are shown in Table 1.

[0206] [Examples 2 to 6]

[0207] Except that the raw material composition was changed as shown in Table 1, the same procedure as in Example 1 was carried out to obtain coating solutions of acrylic adhesive compositions (2) to (6) and adhesive films (2) to (6). These were aged at 50° C. for one day and various evaluations were performed. The results are shown in Table 1.

[0208] [Comparative Examples 1 to 4]

[0209] Except that the raw material composition was changed as shown in Table 1, the same procedure as in Example 1 was carried out to obtain coating solutions of acrylic adhesive compositions (C1) to (C4) and adhesive films (C1) to (C4). These were aged at 50° C. for one day and various evaluations were performed. The results are shown in Table 1.

[0210] [Table 1]

[0211]

[0212] Industrial Applicability

[0213] The adhesive film and the acrylic adhesive composition according to the embodiment of the present invention can be used for so-called flexible devices such as foldable devices and rollable devices.

Claims

1. An adhesive film comprising an adhesive layer composed of an acrylic adhesive, The adhesive strength of the acrylic adhesive to the polyimide film measured at 23° C. at a peeling rate of 10 mm / min and a peeling angle of 180 degrees is 700 gf / 25 mm or more. The adhesive strength of the acrylic adhesive to the polyimide film measured at 23° C. at a peeling speed of 6000 mm / min and a peeling angle of 180 degrees is 1300 gf / 25 mm or more. The storage modulus of the acrylic adhesive at -20°C is less than 140 kPa.

2. The adhesive film according to claim 1, wherein The acrylic adhesive has a shear retention rate of 50% or more.

3. The adhesive film according to claim 1, wherein The acrylic adhesive has a creep value of 45% or more at -20°C.

4. An acrylic adhesive composition, which forms an acrylic adhesive, The acrylic adhesive composition includes an acrylic polymer, an acrylic oligomer, and two or more cross-linking agents.

5. The acrylic adhesive composition according to claim 4, wherein The two or more cross-linking agents include an epoxy-based cross-linking agent.

6. The acrylic adhesive composition according to claim 5, wherein The two or more cross-linking agents include both epoxy-based cross-linking agents and isocyanate-based cross-linking agents.

7. The acrylic adhesive composition according to claim 5, wherein The content of the epoxy crosslinking agent is 0.05 parts by weight or more based on 100 parts by weight of the acrylic polymer.

8. The acrylic adhesive composition according to claim 4, wherein The content of the acrylic oligomer is 5 parts by weight or more based on 100 parts by weight of the acrylic polymer.

9. The acrylic adhesive composition according to claim 4, wherein The acrylic oligomer is a carboxyl-containing acrylic oligomer.

10. The acrylic adhesive composition according to claim 4, wherein The acrylic polymer is a hydroxyl-containing acrylic polymer. 11 . A flexible device comprising the adhesive film according to claim 1 .

Citation Information

Patent Citations

  • Optical recording and reproducing unit

    JP1981000039A

  • Alkailine zinc storage battery

    JP1988076271A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A